Association between colic and sleep problems in infancy and subsequent development, emotional and behavioral problems: a longitudinal study - Lisbeth Valla; Milada Cvancarova Småstuen; Randi Andenæs; Nina Misvær; Christine Olbjørn; Sølvi Helseth (BMC Pediatrics, 2021)
Abstract Background Sleep and colic problems in infancy have been linked to adverse health outcome, but there is limited knowledge of the association between sleep and colic problems in infancy and subsequent development, emotional and behavior problems in young children. The aim of the present study was to examine whether there is an associations between infants’ crying and sleep problems at 6 months and behavioral and development problems at 18 months, 3 and 5 years. Methods This study is based on the Norwegian Mother, Father and Child Cohort Study (MoBa), conducted at the Norwegian Institute of Public Health from June 1999 to December 2008. A total of 86,724 children were included. Colic and sleep (sleep duration, nocturnal awakenings and easy to put to bed) was assessed by mother-reports. Z-scores were used to assess differences between groups of children (e.g. having colic or not, having a sleep problem or not). Emotional and behavioral problems were measured with items from the Child Behavior Checklist. Development problems were measured with items from The Ages and Stages Questionnaire. Results Infants with colic scored significantly lower on development at 5 years (B=-0.10, CI [− 0.14 to - 0.06]) and higher on internalizing problems both at 3 years (B=0.15. CI [0.11 to 0.18]) and 5 years (B=0.17. CI [0.12 to 0.21]) than the reference population. Children who awoke frequently and were more difficult to put to bed at 6 months scored significantly lower on development at 18 months and 3 and 5 years, and higher on internalizing behavior problems at 3 and 5 years (B=0.18 and B=0.16). Children with shorter sleep duration at 6 months had more internalizing behavior problems at 3 years (B=0.14. CI [0.07 to 0.21]) and 5 years (B=0.15. CI [0.05 to 0.25]) than the reference population. Conclusions Colic and sleep problems early in life should be taken into account as risk factors for development and behavioral problems within the first 5 years of a child’s life.